Technique, Experience and the Social Function of Techno Music: A Comparative Analysis of Theodor Adorno and Robert Fink - Pascual, Luciano (2022)
The aim of this article is to deepen reflections on the links between the technical aspects of techno music, the experience of listening to it and its social function. In order to achieve that goal, we carry out a comparative analysis between Theodor Adorno and Robert Fink, which allows us to construct an interpretation of the social dimensions of the techno technique, specifically from the analysis of its teleology and time. This work acknowledges the irreconcilable aspects of the authors; where Fink finds a liberating possibility of manifestation and creation of desire or an expression of an emerging new subjectivity, Adorno finds the innermost fibres of a mechanism of social alienation. These contradictory interpretations, complexified by contributions from other authors (such as Rick Snoman, Mark Butler and Diedrich Diederichsen, Ragnhild Solberg and Juliane Rebentisch), allow us to build a detailed description of the particularities of techno aesthetics.